2016
DOI: 10.1186/s12878-016-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for pulmonary embolism associated with antecedent testosterone or estrogen therapy in patients found to have familial and acquired thrombophilia

Abstract: BackgroundIn patients hospitalized over a 4 year period for pulmonary embolism (PE), we assessed relationships of testosterone (TT) and estrogen therapy (ET) anteceding PE in patients found to have familial-acquired thrombophilia.MethodsFrom 2011 through 2014, 347 patients were hospitalized in Cincinnati Mercy Hospitals with PE. Retrospective chart review was used to identify patients receiving TT or ET before PE; coagulation studies were done prospectively if necessary.ResultsPreceding hospitalization for PE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Particularly since our recent retrospective study of men and women hospitalized for VTE 44 revealed that personal and family history were nonspecific and insensitive to effectively identify subjects in whom TT and estrogen replacement therapy should not be given, prescreening for thrombophilia is realistic. However, it is expensive, with average laboratory costs in our center $1200.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly since our recent retrospective study of men and women hospitalized for VTE 44 revealed that personal and family history were nonspecific and insensitive to effectively identify subjects in whom TT and estrogen replacement therapy should not be given, prescreening for thrombophilia is realistic. However, it is expensive, with average laboratory costs in our center $1200.…”
Section: Discussionmentioning
confidence: 99%
“…36 Use of TT in men affected by late onset hypogonadism (LOH), 37,38 where low T has no definable etiology beyond aging and/or chronic disease, is controversial, with concerns over its effectiveness and safety. 2,[39][40][41][42] Indiscriminate use of TT for LOH is a real issue, 2,4,5,[43][44][45] as this form of therapy is administered to almost 1 in 25 American men over the age of 60. 46 Increasing use of TT may have thrombotic 12,13,[47][48][49][50] and cardiovascular ramifications.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified five ongoing RCTs (IRCT2015101218603N2; EudraCT 2012-000353-31; Madderom 2016; NCT02173951; NCT02435212), and two studies awaiting classification (Antmen 2013; NCT00004982). We did not identify any cluster-randomised trials, NRSIs, CBA or ITS studies that met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Of the five ongoing trials, two compare medication interventions in thalassaemia and two in SCD and thalassaemia (EudraCT 2012-000353-31; IRCT2015101218603N2; NCT02173951; NCT02435212), and one assesses the effectiveness of group medical appointments on self-efficacy and adherence in SCD (Madderom 2016). Of the two studies awaiting classification, one is an educational study (Antmen 2013), and one is a medication intervention (NCT00004982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation